2018
DOI: 10.1177/0309364618775443
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum foot insoles reduce plantar forefoot pressure and increase foot comfort for motorcyclists

Abstract: In this study, an aluminum insole in a motorcycling boot was shown to decrease maximum pressure on the foot. Comfort was significantly higher than that from ethylene vinyl acetate or commercial boot inserts. This increased comfort and decreased pressure should result in increased safety and control for motorcyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…Notably, Bousie et al analysed the variation of the plantar pressures using templates with different hardness during cycling, concluding that contoured templates raised contact area in cycling [31]. Further, Casado et al described changes in motoriders' plantar pressures using different custom foot insoles with different hardness when subjects rode on a motorcycle simulator, resulting in metatarsal foot heads and hallux pressures decreasing with the hardest custom foot insoles [34].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Bousie et al analysed the variation of the plantar pressures using templates with different hardness during cycling, concluding that contoured templates raised contact area in cycling [31]. Further, Casado et al described changes in motoriders' plantar pressures using different custom foot insoles with different hardness when subjects rode on a motorcycle simulator, resulting in metatarsal foot heads and hallux pressures decreasing with the hardest custom foot insoles [34].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Bousie et al [36] found that contoured insoles increased the contact area of the foot in stationary cycling. In addition, Casado et al reported variations in motorcycle riders’ plantar pressures with different CFIs when riding in a motorcycle simulator, concluding that metatarsal and hallux pressures decreased with the hardest CFI [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the simulator CKU28 ® (Mecanitzats Muntada SL, Manlleu, Spain), the riders drove the Circuit of the Americas race (Austin, TX, USA) in which professional sport motorcyclists compete [17]. During the simulation, riders drove the race course, making the same movements as real circuit motorcycle riders would need to make.…”
Section: Methodsmentioning
confidence: 99%
“…All the participants mentioned higher comfort with hard insoles and the lowest values in plantar pressure. Their conclusion was that hard insoles reduce plantar pressures due to the impact and vibration in the foot on the footpegs, increasing comfort and performance [25]. Metatarsal fractured bones was the most common foot injury in motorcycle trauma [26].…”
Section: Discussionmentioning
confidence: 99%